Acute and long-term effects of static stretching on muscle-tendon unit stiffness: A systematic review and meta-analysis - Takeuchi, K.; Nakamura, M.; Fukaya, T.; Konrad, A.; Mizuno, T. (Journal of Sports Science & Medicine, 2023)
Static stretching can increase the range of motion of a joint. Muscle-tendon unit stiffness (MTS) is potentially one of the main factors that influences the change in the range of motion after static stretching. However, to date, the effects of acute and long-term static stretching on MTS are not well understood. The purpose of this meta-analysis was to investigate the effects of acute and long-term static stretching training on MTS, in young healthy participants. PubMed, Web of Science, and EBSCO published before January 6, 2023, were searched and finally, 17 papers were included in the meta-analysis. Main meta-analysis was performed with a random-effect model and subgroup analyses, which included comparisons of sex (male vs. mixed sex and female) and muscle (hamstrings vs. plantar flexors) were also performed. Furthermore, a meta-regression was conducted to examine the effect of total stretching duration on MTS. For acute static stretching, the result of the meta-analysis showed a moderate decrease in MTS (effect size = -0.772, Z = -2.374, 95% confidence interval = -1.409 - -0.325, p = 0.018, I2 = 79.098). For long-term static stretching, there is no significant change in MTS (effect size = -0.608, Z = -1.761, 95% CI = -1.284 - 0.069, p = 0.078, I2 = 83.061). Subgroup analyses revealed no significant differences between sex (long-term, p = 0.209) or muscle (acute, p =0.295; long-term, p = 0.427). Moreover, there was a significant relationship between total stretching duration and MTS in acute static stretching (p = 0.011, R2 = 0.28), but not in long-term stretching (p = 0.085, R2 < 0.01). Whilst MTS decreased after acute static stretching, only a tendency of a decrease was seen after long-term stretching.